Automatic Fish Feeder and Telegram Based Aquarium Water Level Monitoring - Bagas Dewantara; Indah Sulistiyowati; Jamaaluddin Jamaaluddin (Universitas Ahmad Dahlan, 2023)
An important factor in maintaining fish in an aquarium is the timeliness of feeding fish. Most fish keepers are worried about the aquarium's feeding and water conditions, which must be done every day. Therefore, an automatic fish feeding tool and telegram-based monitoring of aquarium water levels were made to make it easier for fish keepers and aquarium owners to provide and monitor fish feed automatically according to a predetermined schedule. Monitoring the remaining feed and water level in the aquarium is done via Telegram. The components used in this tool are Esp 8266 as a microcontroller, RTC as a timer for scheduling fish feed, Ultrasonic as a detector for remaining fish feed, JSN-SR04T as a water level detector, LCD to display time and date as well as notifications and a servo motor functions to open and close the fish feed. The conclusion from the results obtained from this device is that the device works well and helps the aquarium owner to monitor and feed efficiently, despite some challenges such as delay due to poor internet connection.